Morphological differentiation of the complex Pristurus sokotranus (Squamata: Sphaerodactylidae) from Socotra (Yemen) - Sancho, Vicent; Vasconcelos, Raquel; Llorente, Gustavo; Santos, Xavier (Zootaxa, 2017)
Islands are excellent geographic scenarios to study speciation and diversification processes. Among non-volant tetrapods, reptiles are a model group to illustrate these processes due to their low over-sea dispersal. Although biodiversity catalogues are rather complete on islands, remote archipelagos still show high levels of undescribed diversity, including several remarkable examples of cryptic and unrecognized diversity. This should be investigated using integrative approaches, including both morphological and molecular data. The Socotra Archipelago (Yemen), is one of the most isolated continental archipelagos worldwide where a recent barcoding study has identified high levels of undescribed diversity within the reptile community. For example, the endemic semaphore gecko Pristurus sokotranus, the commonest reptile species of the archipelago, is recovered as paraphyletic (with the species P. samhaensis endemic to Samha and Dharsa branching inside it) and shows three geographically structured deep mitochondrial lineages within Socotra Island. To further analyse this, we examined 28 morphological characters (pholidotic, biometrics, and colouration) of P. sokotranus in order to uncover traits that differentiate the three mitochondrial clades. General Linear Models identified a set of traits that differed among clades and sexes. The rate of correct assignment to lineages using a discriminant analysis was 90.90% for males and 90.62% for females. The three clades showed differences in elevation and microhabitat preferences, as well as spatial structure on their distribution range on Socotra. These results corroborate the barcoding study and help to identify P. sokotranus individuals of each clade in the field. Our study further suggests the need of future integrative taxonomic studies including the species P. samhaensis and nuclear markers to revise the current taxonomy of P. sokotranus.